Effects of heterodimeric bone morphogenetic protein‐2/7 on osteogenesis of human adipose‐derived stem cells. (15th October 2015) - Zhang, Xiao; Guo, Jing; Wu, Gang; Zhou, Yongsheng
Abstract: Objective: Roles of bone morphogenetic proteins (BMPs) on osteogenesis of human adipose‐derived stem cells (hASCs) remain ambiguous. In this study, we evaluated in vitro and in vivo functional characteristics of BMPs of different dimerization types, with the aim of determining osteoinductive efficiency of heterodimeric BMP‐2/7 on osteogenesis of hASCs. Materials and methods: We explored osteoinductive effects of three different BMPs by using cell DNA assay, alkaline phosphatase (ALP) activity assay, alizarin red staining and mineralization assay, and real‐time PCR, in vitro . Also, we examined ectopic bone formation in nude mice by using soft X‐ray, histomorphometric and immunohistochemical analyses in vivo . Results: In our dose–response study, we showed that BMPs with both dimerization types did not induce in vitro osteogenesis of hASCs without osteogenic medium (OM). In the presence of OM, BMPs significantly enhanced hASC osteogenesis in a dose‐dependent manner. In in vivo experiments, our analyses indicated that BMPs promoted osteogenesis of hASCs without in vitro osteogenic induction. However, both in vitro and in vivo, there were no significant differences in hASC osteogenic induction between heterodimeric and homodimeric BMPs. Conclusions: Heterodimeric BMP‐2/7 significantly promoted osteogenesis of hASCs in vitro and in vivo . However, BMP‐2/7 was not found to be a stronger inducer of osteogenesis compared to homodimeric either BMP‐2 or BMP‐7.